Pendampingan Perancangan Identitas Visual dalam Upaya Pembentukan Citra Produk Dage Mekarsari - Utami, Gladi Pawestri; Pratama, Aiza Yudha; Paradise, Paradise (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2024)
Mekarsari is a group of dage craftsmen in Ciberung Village, Ajibarang District, Banyumas Regency. Dage itself is a superior product from Ciberung Village which is part of the One Village One Product (OVOP) program. However, Mekarsari's dage product is currently facing a major problem, namely low selling price. This problem is influenced by several factors, including the product's lesser-known image and traditional marketing techniques. To overcome these problems, community service activities are carried out that focus on creating a visual identity for Mekarsari dage, including logo design, which is expected to improve the image of Mekarsari dage products in the eyes of consumers. With a strong and attractive visual identity, Mekarsari dage products are expected to increase their selling value. This activity involves active participation from the Mekarsari Dage craftsmen group, to ensure that the designed visual identity is in accordance with local characteristics and values. The result of this service is the creation of a visual identity that is able to improve the product image. So as to have a positive impact on the local economy.